Analysing the funding policy of a professional academic institution: case of ICSAZ - Masawu, Rumbidzai (Midlands State University, 2017)
The core aim of the study was to analyse the funding policy of ICSAZ. The research has been carried out against the background of financial constraints, widening funding gap and decrease in revenue which led to decreasing profits and failure to raise required capital for desired capital projects. The research used both qualitative and quantitative research methods. To collect data from respondents the researcher used questionnaires and interviews. This was facilitated principally with the help of the Likert Scaling model. The main sources of related literature were internet journals, accounting text books university website library and many more. The researcher used graphs and tables for data presentation and analysis. All variables were established to be noteworthy, the results showed that the Institute has a funding policy that is in blue print, however the policy is not properly communicated within the organisation. The study provided recommendations to management, council, employees and the finance committee of the institute, in connection with best funding policy practise. The recommendations included engaging in partnerships with strategic partners for financing research and education at professional level across the globe and forming strategic alliances with corporate members as financers and the institute as a trainer of company employees